2020
DOI: 10.31234/osf.io/uetg6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cultural similarity among co-religionists within and between countries

Abstract: Cultural evolutionary theories suggest that world religions have contributed to the expansion of human cooperation, in part by consolidating beliefs, values, and practices within a culturally integrated super-ethnic identity. To test this hypothesis, we measured cultural distance between religious groups within and between countries, using the Cultural Fixation Index (CF_ST) applied to the World Values Survey (88 countries, N=243,118). We found cultural similarity between co-religionists within and across coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Here, we specifically focus on cultural trait diversity, which can but does not necessarily correlate with these other characteristics. For example, Americans with different ancestries may possess similar WEIRD psychology [79]. Cultural trait diversity also partially overlaps with challenging aspects of psychology, norms and institutions, such as racism, prejudice, xenophobia, sexism, other forms of discrimination, power differences, and social and economic inequalities.…”
Section: Cultural Evolvability Applied To the Paradox Of Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we specifically focus on cultural trait diversity, which can but does not necessarily correlate with these other characteristics. For example, Americans with different ancestries may possess similar WEIRD psychology [79]. Cultural trait diversity also partially overlaps with challenging aspects of psychology, norms and institutions, such as racism, prejudice, xenophobia, sexism, other forms of discrimination, power differences, and social and economic inequalities.…”
Section: Cultural Evolvability Applied To the Paradox Of Diversitymentioning
confidence: 99%
“…White et al . [79] focus on cultural distance between religions. Handley and Mathew focus on cultural distance between pastoralist ethnic groups.…”
Section: Resolving the Paradox Of Diversitymentioning
confidence: 99%
“…Researchers who have investigated sexual morality have examined moral prohibitions surrounding incest (e.g., Lieberman & Smith, 2012), individual differences in judgments surrounding same-sex sexual behavior (e.g., Pinsof & Haselton, 2016), the association between religious commitment and reproductive strategies (e.g., Hone et al, 2021), the association between disgust and moral judgments of sexual behaviors (e.g., Wang et al, 2019), similarities in sexual morality across cultures (e.g., White et al, 2020), and attitudes toward recreational drug use based on reproductive strategies (e.g., Kurzban et al, 2010). For example, Weeden and Kurzban (2013) and Hone et al (2021) found that religious individuals provided harsher moral judgments toward atypical sexual behaviors (e.g., same-sex sexual behavior) than less-religious people.…”
Section: A Missing Link: the Study Of Sexual Moralitymentioning
confidence: 99%
“…These studies, although making important advances, assess attitudes toward a limited set of sexual behaviors in isolation, often relying on indices such as the World Values Survey (e.g., Weeden & Kurzban, 2013; White et al, 2020). As a result, previous research does not cover the full range of adaptive problems that individuals may face within the realm of sexuality.…”
Section: A Missing Link: the Study Of Sexual Moralitymentioning
confidence: 99%